2019
DOI: 10.1186/s12711-019-0512-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genome analyses reveal the unique genetic composition and selection signals underlying the phenotypic characteristics of three Chinese domestic goat breeds

Abstract: BackgroundAs one of the important livestock species around the world, goats provide abundant meat, milk, and fiber to fulfill basic human needs. However, the genetic loci that underlie phenotypic variations in domestic goats are largely unknown, particularly for economically important traits. In this study, we sequenced the whole genome of 38 goats from three Chinese breeds (Chengdu Brown, Jintang Black, and Tibetan Cashmere) and downloaded the genome sequence data of 30 goats from five other breeds (four non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 121 publications
(151 reference statements)
3
46
0
Order By: Relevance
“…Study of genetic diversity plays an important role in the conservation and utilization of germplasm resources, revelation of evolutionary history, and investigation of phylogenetic relationships. The number of the detected SNPs in the Du’an goat (~17M) was lower than that in the Moroccan (~33M) and Korean indigenous (~37M), and higher than that in the Tibetan Cashmere (~12M), Chengdu Brown (~10M), and Jintang Black goat (~12M) [ 8 ], which could be explained by the difference in the number of individuals, reference genome, detection method, filtering criteria, or breed. The average nucleotide diversity in the Du’an goat was lower than that in the Iranian indigenous goat, while it was found to be higher than that in the Nubian and Korean indigenous goat.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Study of genetic diversity plays an important role in the conservation and utilization of germplasm resources, revelation of evolutionary history, and investigation of phylogenetic relationships. The number of the detected SNPs in the Du’an goat (~17M) was lower than that in the Moroccan (~33M) and Korean indigenous (~37M), and higher than that in the Tibetan Cashmere (~12M), Chengdu Brown (~10M), and Jintang Black goat (~12M) [ 8 ], which could be explained by the difference in the number of individuals, reference genome, detection method, filtering criteria, or breed. The average nucleotide diversity in the Du’an goat was lower than that in the Iranian indigenous goat, while it was found to be higher than that in the Nubian and Korean indigenous goat.…”
Section: Discussionmentioning
confidence: 99%
“…The average r 2 in 50 Kb in the Du’an goat was higher than that in the Iranian indigenous, Moroccan indigenous, and Boer goat, while it was lower than that in the Nubian goat ( Table 2 ). However, ROH-based inbreeding coefficient (0.0025) was lower in the Du’an goat than the Chengdu Brown (0.194), Tibetan Cashmere (0.068), Moroccan indigenous (0.085), and Jintang Black goat (0.119) [ 8 ]. The revelation of individual ROH may help the conservation of this breed, since animals with high levels of ROH could be excluded or assigned lower priority for mating to minimize the loss in genetic diversity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the FGF5 gene demonstrated the relation to coat hair length in mice [50], dogs [51], cats [52], humans [53], donkeys [54] and alpacas [55]. The same selection target has been described in a number of cashmere goat investigations [10,56]. In addition, disruption of the FGF5 gene via the CRISPR/Cas9 system in cashmere goats increased the number of secondary hair follicles and enhanced the ber length [57].…”
Section: Discussionmentioning
confidence: 75%
“…Previous studies have found a few SNP variants of the FGF5 gene that may be associated with hair length, including a missense SNP (c.284G> T) in dogs, four SNPs (c.194C>A, c.182T>A, c.474delT and c.475A>C) in cats, two SNPs (c.433_434delAT and c.245G> A) in donkeys and a missense SNP (c.499C>T) in alpacas [51,52,54,55]. Recently, one SNP (c.253G>A) in the 5'-UTR of FGF5 resulted in a start codon that could lead to a premature/dysfunctional protein in Tibetan cashmere goats [56].…”
Section: Discussionmentioning
confidence: 99%